Prenatal Diagnosis of a Mosaic Paternal Uniparental Disomy for Chromosome 14: A Case Report of Kagami–Ogata Syndrome - Li, Fenxia; Liu, Siping; Jia, Bei; Wu, Ruifeng; Chang, Qingxian (Frontiers in Pediatrics, 2021)
Kagami-Ogata syndrome (KOS) is a rare imprinting disorder with a distinct clinical phenotype. In KOS, polyhydramnios is associated with a small bell-shaped thorax and coat-hanger ribs. The genetic aetiology of KOS includes paternal uniparental disomy 14 [upd(14)pat], epimutations, and microdeletions affecting the maternally derived imprinted region of chromosome 14q32.2. More than 77 KOS cases have been reported. However, only one mosaic upd(14)pat case has been reported. Here, we report a second mosaic upd(14)pat case. The prognosis of upd(14)pat patients is poor because of severe respiratory insufficiency. We summarized prenatal ultrasound findings of KOS here to raise awareness of this condition for possible diagnosis of KOS prenatally, when polyhydramnios in combination with a small bell-shaped thorax and other related features. Prenatal diagnosis using Methylation-Specific Multiplex Ligation-dependent Probe Amplification (MLPA) or a single nucleotide polymorphism-based microarray analysis should be recommended.